Microfactory model for manufacturing new generation electric vehicles - TUNABOYLU, BAHADIR (My University, 2022)
The electromobility presents a potential opportunity for nations to develop and produce their domesticcars especially for emerging markets. This paper proposes a new concept, called microfactory, formanufacturing Electric Vehicles (EV). It is a big challenge for newcomers to enter the automotivemarket as this industry remains heavily under the control of large OEMs (Original EquipmentManufacturer). There are three main de facto monopolies in the automotive industry; the firsttwo of them are the required technology and knowledge to manufacture the Internal CombustionEngine (ICE) and the chassis, and the third one is the difficulty of reaching government funding.The microfactory represents an alternative solution to overcome the existing monopolies with theelectric motor, a tubular chassis, and a novel business model respectively. A detailed analysis of thedifference between conventional techniques and new production paradigm is presented in this work.The principles of the microfactory from the layout to the supply chain management including thesharing economy are presented. This study indicates that the microfactory is a sustainable productionmodel for manufacturing of safe, secure, customized and efficient urban electric vehicles using smartmanufacturing tools in small-scale production with low investment. The aim of this paper is to proposea new disruptive manufacturing method that allows a quicker entry for new players to the automotiveindustry especially for EVs.

Bu çalışmanın öncelikli amacı, sayıları az büyük otomotiv üreticilerinin tekelinde olan sektöre yeni bir üreticinin girmesine olanak sağlayan yeni bir üretim konsepti sunmaktır. Mikrofabrika konsepti ile içten yanmalı konvensiyonel araç üreticilerinin domine ettiği sektörde yeni nesil elektrikli konsept araçların üretimi için kobilere ve yerli otomobilini üretmek isteyen ülkelere rekabet edilebilir bir alternatif sağlanmaktadır. Geleneksel otomotiv üretimi, içten yanmalı motor ve şasiyi üretmek için gerekli teknoloji ve bilgi birikimi, ve devlet teşviklerine ulaşmanın zorluğu nedeniyle birkaç büyük OEM (Orijinal Ekipman Üreticisi)’in kontrolü altındadır. Mikrafobrika konsepti bu zorluklara karşı sırasıyla elektrik motor, tubuler şasi yapısı ve paylaşım ekonomisine dayanan iş modeli sunarak yeni üreticilere pazarda bir fırsat yaratmaktadır. Makalede mikrofabrika teriminin literatürdeki karşılıkları analiz edilmiş, ve bu çalışma kapsamında sunulan konseptle literaturden farklı olarak elektrikli araç üretimi için özgün bir mikrofabrika yöntemi tarif edilmiştir. Konvansiyonel teknikler ile yeni üretim paradigması arasındaki farkın ayrıntılı bir analizi yapılmıştır. Mikrofabrika konsepti için, yerleşim planı, operasyon aşamaları, paylaşım ekonomisine dayanan tedarik zinciri yapısı ve iş modeli detaylarıyla sunulmuştur. Önerilen yöntem sürdürülebilirlik açısından da incelenmiştir. Bu çalışma, mikrofabrikanın, akıllı imalat araçlarını kullanarak, düşük ölçekli yatırımla küçük ölçekli üretimde güvenli, kişiselleşmeye uygun ve verimli şehir tipi elektrikli araçların üretimi için sürdürülebilir bir üretim modeli sunduğunu göstermektedir.
Mikrofabrika yöntemiyle yeni nesil elektrikli araç üretimi
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Akıllı üretim; elektrikli araçlar; esnek üretim sistemleri; mikrofabrika yöntemi; otomotiv endüstrisi; sürdürülebilir üretim; Automotive industry; electric vehicles; flexible manufacturing; microfactory; smart manufacturing; sustainable production